Ihtikār dalam Perspektif Ekonomi Islam dan Sistem Ekonomi Indonesia Implikasi terhadap Keadilan Pasar dan Regulasi - Riza Rasyid Al-Aufa Siagian (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2026)
Ihtikār refers to the economic practice of hoarding goods with the intention of controlling supply and manipulating prices to obtain excessive profits. This practice may lead to market distortion, artificial scarcity, and harm to consumers as well as small-scale business actors. This article aims to analyze the concept of ihtikār from the perspective of Islamic economics and to examine its implications for market justice and regulation within the Indonesian economic system. This study employs a qualitative approach using normative–conceptual analysis through a review of classical and contemporary Islamic economic literature, as well as Indonesian regulations related to competition law and consumer protection. The findings indicate that ihtikār is strictly prohibited in Islamic economics as it contradicts the principles of justice (‘adl), public welfare (maṣlaḥah), and market equilibrium. In the Indonesian context, although regulations prohibiting monopolistic practices and unfair competition have been established, practices resembling ihtikār may still occur due to weaknesses in supervision and law enforcement. Therefore, integrating Islamic economic values into the national regulatory framework is essential to strengthen market justice and maintain economic stability. This study is expected to contribute to the development of Islamic economic literature and to serve as a reference for formulating more equitable and welfare-oriented economic policies.